Oral Health and Risk of Arthritis in the Scottish Population: Results from the Scottish Health Survey - Hadeel Mohammed Abbood; George Cherukara; Ejaz Pathan; Tatiana V. Macfarlane (Stilus Optimus, 2017)
Objectives: To investigate the link between self-reported oral health and arthritis in the Scottish population using data from the Scottish Health Survey. Material and Methods: Data were available from 2008 to 2013 on self-reported arthritis, oral health conditions and oral hygiene habits from the Scottish Health Survey. Arthritis was defined in this survey by self-reported long standing illness, those who reported having arthritis, rheumatism and/or fibrositis. Oral conditions were defined by self-reported bleeding gums, toothache, biting difficulties and/or edentulousness. Oral hygiene habits were defined by self-reported brushing teeth and/or using dental floss on daily basis. Logistic regression was used for statistical analysis adjusted for age, gender, qualification, smoking and body mass index. Results: Prevalence of self-reported arthritis was 9.3% (95% confidence interval [CI] = 9.03 to 9.57). Those who reported having bleeding gums (adjusted odds ratio [OR] = 1.63; 95% CI = 1.35 to 1.96), toothache (OR = 1.32; 95% CI = 1.16 to 1.5), biting difficulties (OR = 1.95; 95% CI = 1.62 to 2.34), and being edentulous (OR = 1.22; 95% CI = 1.08 to 1.37) had an increased risk of arthritis. Brushing teeth (OR = 1.25; 95% CI = 0.74 to 2.12), and using dental floss (OR = 1.11; 95% CI = 0.89 to 1.39) were not associated with arthritis. Conclusions: Self-reported oral conditions were associated with increased risk of self-reported arthritis. Oral hygiene habits were not associated with self-reported arthritis. Further investigation is required to assess the causal association between oral hygiene, oral disease and arthritis.